Merchandise Djampie Oesodo Sebagai Brand Awarness Konsumen - Hanafi, Ahmad Nur; Happy, Handry Rochmad Dwi; Hendrawan, Faldi (Jurnal Desain Komunikasi Visual Asia, 2024)
The existence of herbal medicine has begun to decline because it has been replaced by modern medicines. For the people of Indonesia, herbal medicine is not just traditional medicine, but a drink to support health. The purpose of this research is to create a way to create a new image of herbal medicine that can be a solution to this phenomenon so that it can be considered a casual drink that can be consumed every day. Literature Study, By studying reference books and journals related to today's design techniques and styles and the application of business in the digitalization era. Observations, indirect observations made through digital media related to the development of visual style, observing products that have been in business for a long time, and following issues that develop in society. Analysis, and research on Segmentation, Targeting and Positioning to find out the right strategy in designing brand identity. This research produces 3 types of visual identity and merchandise, namely logo, packaging, and promotional media. The results of the test using the questionnaire method show that the Visual Identity design can provide a value of trust and attract consumers to buy products. Djampie oesodo is a traditional beverage brand that has just been pioneered so the identity of the product is not yet well known. With the use of visual identities such as logos (logograms and logotypes), 1st Packaging, 2nd Packaging, key chains, bags, tumblers, social media, and online stores have been able to become product identities so that buyers can easily identify these products.